Economics of climate change : sensitivity analysis of social cost of carbon - Torniainen, Sami (2016)
Social cost of carbon (SCC) is the key concept in the economics of climate change. It measures the economic cost of climate impacts. SCC has influence on how beneficial it is to prevent climate change: if the value of SCC increases, investments to low-carbon technology become more attractive and profitable.